(untitled) (ModaPalavra e-periódico, 2011)
This work evaluates the professional uniforms for the public cleanness’ workers, taking into consideration some aspects for the production. Such as the risks that the job can offer, aspects of ergonomics, the models, selection of the fabric; it tries to achieve a design of a uniform that will attend to all needs of the public cleanness’ workers. For that, search in this study make important observations, which contributed for the development new products of uniforms more appropriate of the needs the public cleanness’ workers; offering more comfort and safety necessary for well-being at work.